Tracing the source of bottled water using stable isotope techniques - Rangarajan, R.; Ghosh, P.
The Indian Summer Monsoon (ISM)precipitation recharges ground water aquifers in a large portion of the Indian subcontinent. Monsoonal precipitation over the Indian region brings moisture from the Arabian Sea and the Bay of Bengal (BoB). A large difference in the salinity of these two reservoirs, owing to the large amount of freshwater discharge from the continental rivers in the case of the BoB and dominating evaporation processes over the Arabian Sea region, allows us to distinguish the isotopic signatures in water originating in these two water bodies. Most bottled water manufacturers exploit the natural resources of groundwater, replenished by the monsoonal precipitation, for bottling purposes. The work presented here relates the isotopic ratios of bottled water to latitude, moisture source and seasonality in precipitation isotope ratios. We investigated the impact of the above factors on the isotopic composition of bottled water. The result shows a strong relationship between isotope ratios in precipitation (obtained from the GNIP data base)/bottled water with latitude. The approach can be used to predict the latitude at which the bottled water was manufactured. The paper provides two alternative approaches to address the site prediction. The limitations of this approach in identifying source locations and the uncertainty in latitude estimations are discussed. Furthermore, the method provided here can also be used as an important forensic tool for exploring the source location of bottled water from other regions.
Keywords: STABLE ISOTOPE; ISOTOPES; WATER LINE